Stomatal behavior following mid- or long-term exposure to high relative air humidity: A review - Fanourakis, Dimitrios; Aliniaeifard, Sasan; Sellin, Arne; Giday, Habtamu; Körner, Oliver; Rezaei Nejad, Abdolhossein; Delis, Costas; Bouranis, Dimitris; Koubouris, Georgios; Kambourakis, Emmanouil; Nikoloudakis, Nikolaos; Tsaniklidis, Georgios (My University, 2020)
High relative air humidity (RH ≥ 85%) is frequent in controlled environments, and not uncommon in nature. In this review, we examine the high RH effects on plants with a special focus on stomatal characters. All aspects of stomatal physiology are attenuated by elevated RH during leaf expansion (long-term) in C3 species. These include impaired opening and closing response, as well as weak diel oscillations. Consequently, the high RH-grown plants are not only vulnerable to biotic and abiotic stress, but also undergo a deregulation between CO2 uptake and water loss. Stomatal behavior of a single leaf is determined by the local microclimate during expansion, and may be different than the remaining leaves of the same plant. No effect of high RH is apparent in C4 and CAM species, while the same is expected for species with hydropassive stomatal closure. Formation of bigger stomata with larger pores is a universal response to high RH during leaf expansion, whereas the effect on stomatal density appears to be species- and leaf side-specific. Compelling evidence suggests that ABA mediates the high RH-induced stomatal malfunction, as well as the stomatal size increase. Although high RH stimulates leaf ethylene evolution, it remains elusive whether or not this contributes to stomatal malfunction. Most species lose stomatal function following mid-term (4–7 d) exposure to high RH following leaf expansion. Consequently, the regulatory role of ambient humidity on stomatal functionality is not limited to the period of leaf expansion, but holds throughout the leaf life span.
Keywords: Evaporative demand; Stomatal closing ability; Stomatal size; Transpiration; Water loss